The Influence of E-Commerce Features on Purchasing Decisions (Case Study on Management Department Students, Faculty of Economics, State University of Medan) - Manik, Enjelia; Wahyuni, Futri; Manurung, Grace Silvia; Khaira, Imamul; Siregar, Zulkarnain (Economic: Journal Economic and Business, 2024)
This research was conducted with the aim of finding out how much influence e-commerce has on purchasing decisions among students majoring in management at the Faculty of Economics, Medan State University. The method used in this research is a quantitative method, with data analysis techniques using simple linear regression analysis. The data used is a questionnaire. The research results show that E-commerce features partially have a significant effect on purchasing decisions. Hypothesis testing shows that there is an influence of e-commerce on purchasing decisions among students majoring in management, Faculty of Economics, Medan State University. The value of the equation Y = 8.940(?) +0.686 (X) + e. The coefficient of determination R Square value of 0.162 means that e-commerce features influence purchasing decisions by 16.2%, while the remaining 83.8% is influenced by other factors.